The regulation of human blastoid research: A bioethical discussion of the limits of regulation. (14th September 2022) - Sawai, Tsutomu; Akatsuka, Kyoko; Okui, Go; Minakawa, Tomohiro
Abstract : The creation of human blastoids holds great potential for research on early human development but also raises considerations about the ethics of such research and its regulation.